What is at stake in a war? A prospective evaluation of the Ukraine and Russia conflict for business and society. Issue 6 (25th April 2022) - Lim, Weng Marc; Chin, Markson Wee Chien; Ee, Yaw Seng; Fung, Chorng Yuan; Giang, Carolina Sandra; Heng, Kiat Sing; Kong, Melinda Lian Fah; Lim, Agnes Siang Siew; Lim, Bibiana Chiu Yiong; Lim, Rodney Thiam Hock; Lim, Tze Yin; Ling, Chui Ching; et al.
Abstract: War produces devastating impacts on humankind, especially in terms of lives and livelihoods. While war is a widely studied topic in history, it remains relatively understudied in business. To address this gap, this article explores the impact of war for business and society. To do so, this article undertakes a prospective evaluation of the Ukraine and Russia conflict as a recent case of war. In doing so, this article reveals that a war can impact society within (e.g., limit access to basic necessities and monetary resources, increase unemployment and reduce purchasing power, and increase asylum seekers and refugees ) and outside (e.g., supply shortage and inflation and threat of false information ) as well as business within (e.g., threat of cyberattacks, threat to digital and sustainable growth, and short‐term and long‐term sanctions and support ) and outside (e.g., test of business ethics and moral obligations and test of brand management ) war‐torn countries . The article concludes with an agenda for future research involving war, business, and society.